Mental health of older adults living in nursing homes in Slovakia – Results of a preliminary study - Sováriová Soósová, Mária; Hazuchová, Lucia (Magyar Gerontológia, 2022)
Loneliness is a serious public health problem of an ageing population. The prevalence of loneliness in elderly population was estimated to rise from 10% to 45%. In elderly population, loneliness is considered as a risk factor for mental health disorders, especially depression. Depression and anxiety are among the most common mental health disorders worldwide and their prevalence is increasing, especially among seniors who are hospitalised and living in nursing homes.